Transport Subsidies, System Choice, and Urban Sprawl - Jan K. Brueckner (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper analyzes the effect of transport subsidies on the spatial expansion of cities, asking whether subsidies are a source of undesirable urban sprawl. While the cost-reducing effect of transport subsidies is offset by a higher general tax burden (which reduces the demand for space), the analysis shows that subsidies nevertheless lead to spatial expansion of cities. If the transport system exhibits constant returns to scale, the subsidies are inefficient, making the urban expansion they entail undesirable. The paper also studies transport system choice.' The city is portrayed as selecting its transport system from along a continuum of money-cost/time-cost choices.
Keywords: 330; transport subsidies; urban sprawl; spatial expansion of cities; transport; urban expansion